Harnessing organic compounds from wastewater for visible-light-driven hydrogen evolution - Peñas-Garzón, Manuel; Drazic. Goran; Silva, Cláudia G.; Faria, Joaquim L.; Sampaio, María J. (Elsevier, 2026)
The increasing demand for hydrogen (H2) as an energy vector has driven the search for novel resources to ensure its supply. This study investigates the valorization of actual urban wastewater (WW) for continuous H2 generation via photocatalysis using g-C3N4-based materials under visible light. Untreated WW revealed lower H2 production than deionized water (e.g., around 150 and 240 μmol·gcat−1·h−1, respectively) due to inhibitory effects of turbidity and organic load. Adjusting the WW pH to ∼3 significantly enhanced H2 production up to around 260 μmol·gcat−1·h−1 (∼80 μmol·gcat−1·h−1 when using deionized water), suggesting increased proton availability, improved pollutant adsorption on the photocatalyst surface, and enhanced electron transfer under acidic conditions. Process efficiency was influenced by operational parameters, with optimal performance at 25 °C and 0.25 g·L−1 of photocatalyst. Organic compounds in WW played a crucial role, as H2 yield declined markedly after their removal, confirming they act as electron donors. The addition of synthetic sacrificial agents, such as triethanolamine (TEOA, 0.05 M), further increased H2 yields up to ∼5900 μmol·gcat−1·h−1, highlighting their strategic role in boosting production. The g-C3N4-based photocatalyst retained activity after reuse and when immobilized on a polymeric film, allowing easy recovery without loss of performance. These findings demonstrate the potential of immobilized photocatalysts for efficient H2 production from urban wastewater.
Keywords: Hidrógeno (Combustible); Aguas residuales; Wastewater streams; Continuous H2 generation; Photocatalysis; Graphitic carbon nitride (g-C3N4); Polymeric film